Contemporary topics 2. CD 3, Units 9-12 academic listening and note-taking skills - Kisslinger, Ellen; Rost, Michael (S.l. : Pearson Longman, 2009)
Features college lectures from several academic disciplines, including architecture, media studies, and culinary arts.
Compact discs.
High intermediate English.
26896
Keywords: Note-taking.; English language -- Spoken English -- Problems, exercises, etc